Potensi Anthelmintik Akar Tanaman Putri Malu (Mimosa pudica L.) terhadap Hymenolepis nana pada Mencit - A A Candra; Y Ridwan; E B Retnani (Media Peternakan, 2008)
The objective of this experiment was to observe the anthelmintic effect of different concentration of root extract of the sensitive plant (Mimosa pudica L.) to Hymenolepis nana (Hymenolepis sp.) in mice. Sixty mice were divided into 6 groups consisting of 10 mice per group. Mice were infected with 100 infective eggs of Hymenolepis sp. after deworming by mebendazol. After reaching the prepaten phase (? 21st day), mice were treated with different concentration of root extract per oral, namely 100%, 50%, 25%, 12.5%. Positive control treated with mebendazole and negative control treated with distilled water. Fecal eggs were counted using McMaster method on day 2, 4, 6 and 8 after treatment. Mice were sacrificed for worm counting of Hymenolepis sp. in mice intestine on the day 10 day after treatment. Efication of the root extract to Hymenolepis sp. in mice for concentration 100%, 50%, 25% and 12.5% were 59.62%, 86.38%, 45.54%, 92.49% respectively. Reducing in the number of Hymenolepis sp. was inconsistency decreasing in the eggs number per gram fecal. Key words: Hymenolepis nana, Mimosa pudica L., anthelmintic